(untitled) (Research, Society and Development, 2025)
This article investigates the limits and advances in the pedagogical practice of mathematics teaching in higher education, based on qualitative research carried out in a university center in Santa Catarina. The objective of the study was to understand teachers’ perceptions about the challenges of teaching mathematics and to identify advances in the supply of pedagogical and technological resources. The methodology adopted was qualitative, with semi-structured interviews applied to professors with a bachelor’s degree in administration and accounting sciences, whose data were analyzed according to Bardin’s content analysis approach. The results reveal that the main challenges of students include deficiencies in basic mathematical content, difficulties in interpretation and mathematical anxiety. The teachers, on the other hand, highlight the need for continuous pedagogical improvement, adaptation to different learning profiles and the search for more dynamic didactic strategies. Regarding advances, the provisions are a greater use of educational technologies and a growing appreciation of active methodologies, without mention of pedagogical or didactic advances. In the debate with the authors, Zabalza, Masetto, Valdeleón, Acosta and Ramírez, Chevellard, Shulmann, Hill. Ball and Schiling, Carrillo-Yañez, Climent et al., it is concluded that the professionalization of teaching and the systematization of practices are essential to overcome the challenges and improve the quality of mathematics teaching.